Hey there!
At first we have find the value of "y",
Finding the value of "y"
Here,
8x + y = 23 - 10x - y = - 27
10(8x + y) = 23 × 10 8 (- 10x - y) = - 27 × 8
80x + 10y = 230 ---> (i) - 80x - 8y = - 216 ----> (ii)
By elimination method,
Equation (i) - (ii)
(80x + 10y) - (-80x - 8y) = 230 - (-216)
=> 80x + 10y + 80x + 8y = 230 + 216
=> 10y + 8y = 446
=> 18y = 446
=> y = 446/18
=> y = 24.7
Putting the value of "y" in Equation (i)
80x + 10y = 230
=> 80x + 10 × 24.7 = 230
=> 80x + 247 = 230
=> 80x = 230 - 247
=> 80x = -17
=> x = -17/80
=> x = - 0.21
Therefore the values of "x" and "y" are
x = -0.21 and y = 24.7
Hope it helps